Cancer Nanotherapy: Investigating Subcellular Compartment Targeting Effect of Porous Coordination Cages for Enhancing Cancer Nanotherapy (Small 47/2018). Issue 47 (26th November 2018) - Fang, Yu; Lian, Xizhen; Huang, Yanyan; Fu, Guo; Xiao, Zhifeng; Wang, Qi; Nan, Beiyan; Pellois, Jean‐Philippe; Zhou, Hong‐Cai
Abstract : In article number1802709, Jean‐Philippe Pellois, Hong‐Cai Zhou, and co‐workers uncover a series of metal‐organic cages as novel and superior cargo delivery scaffolds that target subcellular compartments, such as the nucleus, cytoplasm, and membrane, within a living cell. Through manipulation of the overall charge and surface affinity of the cages, the "nano‐bio" interactions between several cellular barriers and the nano cages can be tuned. This finding provides a unique delivery platform for cell imaging, cancer therapy, and gene editing.